Budaya Dan Iklim Organisasi Di Sekolah - Tasliman, Diana; Suklani, Suklani (Jurnal Ilmiah Wahana Pendidikan, 2024)
The development of effective, efficient, productive and accountableschools needs to be supported by changes in various other aspects ofeducation, including school climate. Changes in the school climate need tobe carried out to respond to today's increasingly deteriorating educationalconditions. This is further strengthened by fundamental changes in variousaspects of life, which require educational adjustments, and a conduciveschool climate that supports meaningful learning. Changes in all aspects oflife are influenced by the rapid development of information andcommunication technology, therefore So that we can adapt to developments over time, climate change and a more up-to-date or up-to-date school culture are very necessary. School climate and culture have a great influence on school members, especially students. It is hoped thatwith conducive climate and cultural conditions, students can feelcomfortable, safe and orderly in studying at school. This research uses aqualitative method, a qualitative method, namely a method that collectsdata using instruments or tests, data collection involves researchers visitingthe researcher's place directly and observing the behavior of the individualsthere without asking questions or conducting interviews. To create apositive school climate, of course, harmonious social relations betweenfellow workers are needed. These social relationships take the form ofvertical and horizontal communication, employee cooperation whileworking, supervision, support from subordinates, and clarity of taskscarried out by workers. In other words, organizational climate is the values,beliefs, traditions and assumptions